Antioxidant Activities and Phenolic Compounds in Fruits of Cultivars of Cornelian Cherry (Cornus mas L.) - Klymenko, Svitlana; Kucharska, Alicja Zofia; Sokół-Łętowska, Anna; Piórecki, Narcyz (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Cornelian cherry (Cornus mas L.) is a plant grown in the Eastern and Southern regions of Europe and the Middle East, where it has been used in domestic cuisines for centuries and is one of the most valuable fruit plants in the family Cornaceae Bercht. et J. Presl. It is a very ancient cultural plant in Ukraine known from times of Kyiv on Rus. It wildly used as a valuable food and medicinal plant. All parts of the plant cornelian cherry widely used in folk medicine for the prevention and treatment of many diseases. The aim of this study was to evaluate the antioxidant activity and phenolics content of Cornus mas 20 cultivars collected in the M.M. Gryshko National Botanical Garden of NAS of Ukraine. The content of the total antioxidant activity and phenolic compounds from the fruits of the Cornus mas twenty cultivars were compared. Antioxidant activity (AOA) was measured using three different photometric methods – DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS (2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) and FRAP (Ferric reducing antioxidant power). Total phenolic content (TPC) was evaluated using the Folin-Ciocalteu reagent assay. The results for AOA (μMol Trolox/g) determined by the DPPH method varied from 5.94 (Kozerog) to 16.56 (Kostia), ABTS method varied from 13.560 (Koralovyj Marka) to 33.96 (Semen), FRAP method varied from 8.45 (Koralovyj) to 22.49 (Kostia). The results for TPC varied from 91.34 (Kozerog) to 289.79 (Bolgarskyj) mg/100g. There was recorded a positive linear correlation between antioxidant activity and total phenolic content in the examined plant material. Obtained data showed that investigated cultivars have a potent antioxidant activity that can be used for further investigation and utilization of cornelian cherry. The results of our study also showed that cornelian cherry is an important traditional plant that deserves special attention for widespread growth in Ukraine due to its high biochemical characteristics, as well as useful nutritional and medicinal properties. The fruits of cornelian cherry are promising sources of biologically active substances. Cornelian cherry fruits are a rich source of nutrients for humans. Currently, this plant is less known and this new source can be potential as a functional food or value-added ingredient in the future in our dietary system.